Composição química e avaliação sensorial de biscoitos elaborados com polpa de pequi (Caryocar brasiliense Camb.) desidratada - MEDEIROS, Priscilla Ramos Mortate da Silva (2009)
This study evaluated the chemical composition of dehydrated pequi pulp and its contribution on the nutritional value and acceptability in cookies. Forced air oven drying (60ºC/24 hours) was used to dehydrate the pequi pulp in three repetitions. Five cookie formulations were developed with dehydrated pulp concentrations of 0% (BPA), 5% (BP5), 10% (BP10), 15% (BP15) and 20% (BP20). The centesimal composition and energy value of bleached pulp, dehydrated pulp and the cookies were determined. The fatty acid profile of the dehydrated pulp was also determined. The cookies were analyzed according to preference, acceptability, physical characteristics and microbiological quality. The data were analyzed using analysis of variance and the Tukey, Friedman and Kolmogorov-Smirnov tests at a 5% significance level. Bleached pequi pulp and dehydrated pequi pulp are rich in lipids (19.39g.100g-1 and 50.79g.100g-1) and dietary fiber (7.45g.100g-1 and 26.68g.100g-1). The energy value of dehydrated pulp was almost three times that of the bleached pulp (204.8 e 525.1 kcal.100g-1). The dehydrated pulp contained 40.53% saturated fatty acids and 51.21% unsaturated fatty acids, with a predominance of oleic acid (47.94%) and palmitic acid (34.45%). The cookie formulations contained 8.16 to 8.90g.100g-1 of moisture, 8.66 to 8.91g.100g-1 of proteins, 12.35 to 13.25g.100g-1 of lipids and from 1.20 to 1.41g.100g-1 of ash. The level of dietary fiber increased significantly with the addition of dehydrated pulp, varying from 2.12 to 5.11g.100g-1 (p<0.05). The cookies energy value varied from 404.6 to 414.0 kcal.100g-1. The width and spread factor of the cookies decreased with the increase in the concentration of the dehydrated pequi pulp. There was no significant difference among the samples as far as preference was concerned. The cookies had good acceptability in regard to appearance, flavor and microbiological quality within the legally established limits. In conclusion, cookies made with dehydrated pequi pulp are a product with good nutritional potential and good acceptability